ПОМОГИТЕ ПОЖАЛУЙСТА
Уровнение:
x*(x+3)*(x-1)= x^2(x+2)

упростить:
а)
(3-4x)*16x+(8x-3)^2
b)
-2x(1-x)+(2x-3)*(x-1)
c)
4(1+3x)^2-24x
d)
(x+4)*(x-4)-(x-3)^2
ПЛИИИИИИИИИИЗЗЗ в долгу не останусь)*

2

Ответы и объяснения

2013-04-24T01:30:27+04:00

уравнение

х(х+3)(х-1)=х²(х+2)

х(х²+2х-3)=х³+2х²

х³+2х²-3х-х³-2х²=0

-3х=0

х=0

 

упростить

а) =48х-64х²+64х²-48х+9=9

б) = -2х+2х²+2х²-5х+3=4х²-7х+3

в) = 4+24х+36х²-24х=36х²+4

г) = х²-16-х²+6х-9=6х-25=

Лучший Ответ!
2013-04-24T01:32:08+04:00

x(x+3)(x-1)= x^2(x+2)\\x(x^2-x+3x-3)=x^3+2x^2\\x^3+2x^2-3x=x^3+2x^2\\-3x=0\\x=0

 

(3-4x)16x+(8x-3)^2=48x-64x^2+64x^2-48x+9=9

 

 

-2x(1-x)+(2x-3)(x-1)=-2x+2x^2+2x^2-2x-3x+3=\\=4x^2-7x+3

 

 

4(1+3x)^2-24x=4(1+6x+9x^2)-24x=\\=4+24x+36x^2-24x=4(1+9x^2)

 

 

(x+4)(x-4)-(x-3)^2=x^2-16-(x^2-6x+9)=\\=x^2-16-x^2+6x-9=6x-25

 

Ну и, я надеюсь, как "Лучшее решение" не забудешь отметить?!... Спасибо!... ;))))